Effects of socio demographic maternal and childhood factors on deciduous dentition among the children in Kalutara district - Perera, K.A.K.D (My University, 2008)
A research project was conducted to study the effects of socio-demographic , maternal and childhoodCharacteristics on deciduous dentition among children in the Kalutara district in order to achieve the following objectives.Study Objectives are to determine the mean eruption time (MET) of the first deciduous tooth and identify socio-demographic, maternal and childhood factors that affect the eruption of the first deciduous tooth.To determine the prevalence of developmental defects in the deciduous dentition and its' association with socio-demographic, maternal and childhood factors. To determine the prevalence of dental caries among two years old children and their association with Socio-demographic , maternal and childhood characteristicsTo assess the relationship of dental caries experience between mothers and their children.Child Welfare Clinic based descriptive study was carried out from June 2006 to December 2007. A cohort of 517 children aged 6-7 months was followed up and at the end of the study period their mean age was 25.3 (SD 0.4) months. Information pertaining to basic socio-demographic, maternal and childhood characteristics was collected by administering a pre-tested validated self-administered questionnaire to the mothers of selected group of children. Study suggested that both prenatal and postnatal nutritional conditions during the Course of deciduous teeth development would play a role in eruption time of first deciduous tooth and development defects of enamel in deciduous teeth. Furthermore, the result of the study was supportive of the multifactor aetiology for dental caries. It's close association with dietary practices and behaviour; life style related aspect was emphasized again.